Photochemical Impact on Ozone Fluxes in Coastal Waters - L. Coleman; P. McVeigh; H. Berresheim; M. Martino; C. D. O'Dowd (Advances in Meteorology)
Ozone fluxes, derived from gradient measurements in Northeast Atlantic coastal waters, were observed to depend on both tide height and solar radiation. Peak ozone fluxes of −0.26±0.04 μg m-2 s-1 occurred during low-tide conditions when exposed microalgae fields contributed to the flux footprint. Additionally, at mid-to-high tide, when water surfaces contribute predominantly to the flux footprint, fluxes of the order of −0.12±0.03 μg m-2 s-1 were observed. Considering only fluxes over water covered surfaces, and using an advanced ozone deposition model that accounts for surface-water chemistry enhancing the deposition sink, it is demonstrated that a photochemical enhancement reaction with dissolved organic carbon (DOC) is required to explain the enhanced ozone deposition during daylight hours. This sink amounts to an ozone loss rate of up to 0.6 ppb per hour under peak solar irradiance and points to a missing sink in the marine boundary layer ozone budget.